Antimicrobial Agents with Anti-tuberculosis Activity Added to Bone Cement - E. O. Peretsmanas; I. A. Gerasimov; V. S. Zubikov; I. V. Esin (Туберкулез и болезни лёгких)
The review analyzes publications devoted to experimental studies of antimicrobial agents with anti-tuberculosis activity added to bone cement.It presents information about the prospects of using antimicrobial agents in bone cement for treatment of infectious joint diseases.